2018
DOI: 10.3390/app8050821
|View full text |Cite
|
Sign up to set email alerts
|

State-of-Health Identification of Lithium-Ion Batteries Based on Nonlinear Frequency Response Analysis: First Steps with Machine Learning

Abstract: Abstract:In this study, we show an effective data-driven identification of the State-of-Health of Lithium-ion batteries by Nonlinear Frequency Response Analysis. A degradation model based on support vector regression is derived from highly informative Nonlinear Frequency Response Analysis data sets. First, an ageing test of a Lithium-ion battery at 25 • C is presented and the impact of relevant ageing mechanisms on the nonlinear dynamics of the cells is analysed. A correlation measure is used to identify the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…In addition to a very diverse range of systems, a wide variety of phenomena can be investigated with nonlinear techniques. Previous works have ranged from detailed studies of electrochemical processes (e.g., determining transfer coefficients α [83] and examining kinetic mechanisms in electrochemical reactions [86] ) to the linkage of important system parameters to nonlinear outcome (e.g., state of health [87] and aging effects of batteries [88] ). Harting et al demonstrated that NL techniques can be used to differentiate between different aging processes in lithium-ion batteries.…”
Section: Nonlinear Electrochemical Methodsmentioning
confidence: 99%
“…In addition to a very diverse range of systems, a wide variety of phenomena can be investigated with nonlinear techniques. Previous works have ranged from detailed studies of electrochemical processes (e.g., determining transfer coefficients α [83] and examining kinetic mechanisms in electrochemical reactions [86] ) to the linkage of important system parameters to nonlinear outcome (e.g., state of health [87] and aging effects of batteries [88] ). Harting et al demonstrated that NL techniques can be used to differentiate between different aging processes in lithium-ion batteries.…”
Section: Nonlinear Electrochemical Methodsmentioning
confidence: 99%
“…Thus, predicting the degradation behavior of batteries by ML techniques is also essential for the entire electrification system. [57][58][59] The fundamental goal of ML models in rechargeable batteries is to establish the quantitative structure-activity relationship (QSAR) between conditional attributes and decision attributes through low-cost and accurate predictions. [60] In this section, we will mainly focus on the recent applications of ML models for predicting properties of materials, state of battery, and designing materials for rechargeable LIBs.…”
Section: Applications Of ML In Rechargeable Libmentioning
confidence: 99%
“…The characteristics of accumulator battery depend on the chemical composition of the components, but, despite this, an equivalent selection of the main characteristics for the traction storage battery is required, since they affect the quality and service life of the traction power source as a whole. Table 1 shows the main characteristics that you need to be guided by when choosing the most preferred type of rechargeable batteries [66][67][68]. To determine the most preferred type of TCS, the following characteristics were selected [68,69]:…”
Section: Comparison Of Different Types Of Batteriesmentioning
confidence: 99%